KEMAMPUAN KOMUNIKASI DAN PEMECAHAN MASALAH MATEMATIS MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR MELALUI PEMBELAJARAN BERBASIS MASALAH - Karlimah (Jurnal Pendidikan, 2010)
This experimental study was conducted to investigate students’ mathematical communication and problem solving abilities by using problem based learning (PBL). The subjects of this study were 67 student teachers from a State University in Bandung. Instruments of this study were a mathematical communication test and a mathematical problem solving test. The data were analyzed by using one and two path anova, Mann Whitney test and chi square test. The study found that: (1) Students’ mathematical communication and problem solving abilities in PBL classroom were higher than those of students of conventional classroom; (2) The advantage of PBL were also supported by the findings that mathematical communication and problem solving abilities of students with low initial ability were higher in PBL classroom compared to those ofconventional classroom; (3) There was significant correlation between mathematical communication and problem solving abilities; (4) There were no interaction between teaching approaches and prior mathematics ability on students’ mathematical communication and problem solving abilities.